Between Ecclesiology and Diplomacy: Francisco de Vargas and the Council of Trent - Tubau, Xavier (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2019)
This article examines the letters and reports of Francisco de Vargas (ca. 1500–66), a jurist who served in different positions under Charles V and Philip II during the three phases of the Council of Trent. Vargas defended the superiority of the council over the pope in matters of faith and practices and drew attention to the need to continue the reform of the Roman Curia started at the Council of Constance. The article examines the way this conciliarist adapted ecclesiology to developing circumstances over the three phases of the Council of Trent, and points out the need to revise the monolithic, papalist view that historiography continues to present of early modern Spanish ecclesiological thought.